Histological study of the pecten oculi and Cornea of the falcon"s eye ball (circus cyaneus c.): Shakir Mahmood Mirhish1 and Samawal Jassim Mohamed Al-Robaae - Mirhish, Shakir Mahmood (The Iraqi Journal of Veterinary Medicine, 2012)
The histological study of the pecten oculi of falcon eyeball is consists from 11-12 pecten plates connected to the pectin bridge. The pectin oculi extending from optic nerve toward the virtous body. Its characterization are highly visualization and continuous capillary network which infiltrated by melanocyte. The pecten oculi without muscles and nerve fibers. The study revealed that cornea of falcon eyeball was characterized by fine curvature, translucent with peripheral thickness. The cornea occupied the quarter of fibrous tunica. It consists from five layers: - anterior corneal epithelium, Bowman's membrane, stroma, Descement's membrane and endothelium.